2005
DOI: 10.1197/j.aem.2004.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Patients Who Leave without Being Seen

Abstract: ED capacity >100% is associated with patients who LWBS and is most significant at 140% capacity. ED capacity of 100% may not be a sensitive measure for overcrowding. Physician factors, especially emergency medicine training, also appear to be important when using LWBS as a quality indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 11 publications
(8 reference statements)
0
33
0
1
Order By: Relevance
“…3 As wait times increase, so do the rate of patients who LWBS. 4,5 Despite recent expansion of health insurance coverage, ED visit volumes are expected to grow, exacerbating ED crowding and LWBS rates. 6 The financial effect of crowding on the costs of ED visits has been previously estimated, [7][8][9][10] but has been limited to hospital (i.e., facility) reimbursement 9,11,12 or patients with disease-specific conditions (e.g., chest pain 13 ) or has considered only the revenue opportunity loss from ambulance diversion.…”
mentioning
confidence: 99%
“…3 As wait times increase, so do the rate of patients who LWBS. 4,5 Despite recent expansion of health insurance coverage, ED visit volumes are expected to grow, exacerbating ED crowding and LWBS rates. 6 The financial effect of crowding on the costs of ED visits has been previously estimated, [7][8][9][10] but has been limited to hospital (i.e., facility) reimbursement 9,11,12 or patients with disease-specific conditions (e.g., chest pain 13 ) or has considered only the revenue opportunity loss from ambulance diversion.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] These patients may be severely ill and experience adverse events as a result of lacking or delayed ED treatment. [7][8][9][10] One study found that 11% of LWBS patients required hospitalization within the next week, including some who underwent emergent surgery.…”
mentioning
confidence: 99%
“…8 High rates of LWBS also reflect lower patient satisfaction, potential violation of the Emergency Medical Treatment and Labor Act (EMT-ALA) by failure to perform a medical screening examination, and potential lost revenue. 1 LWBS rates can be used as one indicator of ED quality. 4,11 However, to do so, a national LWBS rate estimate should be established as a benchmark for comparisons.…”
mentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Certains DAPCM peuvent avoir des codes de triage urgents. 14,20 Les facteurs les plus souvent associés au DAPCM sont : l'achalandage de l'urgence, 5,6,[21][22][23][24] le temps d'attente jugé trop long, 4,5,9,10,17,20,[25][26][27][28][29] l'attribution d'un code de triage moins urgent, 5,6,17,20,27,[30][31][32][33] les caractéristiques intrinsèques du médecin de garde, 21,23 un jeune âge, [5][6]…”
Section: Introductionunclassified